The assessment of maternal deaths between 2015 and 2020 in Elazığ, Turkey - Batmaz, İbrahim; Kavak, Salih Burçin; Çelik Kavak, Ebru; Gül, Evrim; Şanlı, Cengiz; Bulu, Gülay; Keser, Hasan Burak (Perinatal Medicine Foundation, 2020)
Objective: To determine the maternal deaths and the factors affecting them in our city. Methods: The maternal deaths occurred in our city between January 2015 and June 2020 were reviewed retrospectively. The review was conducted by checking "Maternal Death Registry Forms" of the Provincial Directorate of Health. In cases where additional data related with the cause of death were required, the relatives of the cases, associated family practitioner, The Council of Forensic Medicine or local authorities were contacted. The data of the cases including age, gravida, parity, abortion, delivery type, week of gestation during delivery, period of death and maternal deaths due to direct, indirect and incidental causes were recorded. Based on total live births and maternal deaths within 6.5 years, maternal mortality rate was found as the maternal death number per 100,000 live births. Descriptive statistics were used for the statistical analysis of the data. Results: A total of 46.618 live births occurred between 2015 and 2020 in Elazığ. The number of maternal deaths due to direct and indirect causes is 7, and maternal mortality rate was found 15.01/100,000. Hypertensive diseases during pregnancy (n=3, 42.8%), pulmonary embolism (n=1, 14.3%) and cerebral thrombosis (n=1, 14.3%) were among the natural causes of maternal deaths. Indirect cause for maternal death was cardiac diseases (n=2, 28.6%). When they were categorized according to the Three Delays Model, there were 3 death cases in the first delay model and 2 death cases in the third delay model, but there was no maternal death in the second delay model. Conclusion: Maternal death is an significant public health issue which develops due to the generally preventable causes and maintains its importance. The factors contributing to death should be paid attention in order to decrease maternal death rates.